Heterologous Expression of a Potential ‘Paulownia fortunei’ MYB Factor Gene, PfMYB90, Improves Salt and Cold Tolerance in Arabidopsis - Hongling Wang; Shizheng Shi; Guijie Luo; Ruifang Huang; Dezong Sui; Yunpeng Gao; Lei Wang (Plants)
The paulownia tree belongs to the Paulowniaceae family. Paulownia has strong vitality; has strong adaptability to harsh environmental conditions; and can be used as building raw material, as well as processing drugs and having other purposes. In the research field of MYB transcription factors of the paulownia tree, it is rare to discuss the resistance to abiotic stress. The research in this area has not received sufficient attention and depth, which also indicates an important potential direction for future research. In this study, we performed bioinformatics analysis of the stress-related gene PfMYB90, a potential transcription factor, and investigated its mechanism of action under salt and cold stresses. PfMYB90 was strongly expressed in the fully unfolded leaf and root of plants in both stress treatments. Transgenic PfMYB90 Arabidopsis plants had a greater survival rate under salt and cold stresses, and the degree of leaf damage was comparatively smaller, according to phenotypic observation and survival rate calculations. By measuring the corresponding physiological indexes after stress and detecting the expression levels of corresponding stress genes (AtNHX1, AtSOS1, AtSOS2, AtSOS3, AtCBF1, AtCBF3, AtCOR15a, AtRD29a), it was found that after PfMYB90 gene transfer, Arabidopsis showed strong tolerance to salt and cold stresses. This is consistent with the results mentioned above. This transgenic technology enables Arabidopsis to survive under adverse environmental conditions, allowing it to maintain a relatively stable growth state despite salt accumulation and cold stress. Therefore, PfMYB90 may be a key gene in the regulatory network of salt damage and cold damage, as well as one of the key transcription factors for Paulownia fortunei environmental conditions.